(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
In this work, the technological properties of a dry plant extract with a diuretic effect were studied. During the study, the moisture content, fluidity, density, granulometric composition and hygroscopicity of the extract were determined, and their importance in the development of dosage forms was assessed. The results obtained showed that the dry extract is suitable for the preparation of tablet and capsule forms. The storage conditions and technological stability of the extract were also analyzed. The results of the study allow the creation of effective drugs based on the dry diuretic extract.